Quantifying Node Security in Wireless Sensor Networks under Worm Attacks - Ramos, Alex; Aquino, Breno; Filho, Raimir Holanda; Rodrigues, Joel J. P. C. (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
The peculiar characteristics of wireless sensor networks (WSNs) make them vulnerable to physical attacks. Once a sensor node is physically captured by an adversary, it can be modified not only to perform malicious activities to disrupt network operation but also to propagate malicious worms to infect other nodes. In the face of such a threatening scenario, the system administrator needs to be aware of which nodes may have been compromised, so that appropriate countermeasures can be taken in a timely fashion. This paper presents the Sensor Security Status (S3), a security metric model for estimating in an online manner the probability that a sensor node has been infected, based on both the interaction among nodes and the alerts from the intrusion detection system (IDS). Simulation results show that S3 can accurately estimate node security level with low performance overhead and power consumption.